Sun protection factor and tyrosinase inhibitory activity of several plant secondary metabolites - Raihana Mufliha Fatharani; Ula Aulia Fitrian; Sumail Sidik Ode Ishak; Amirah Adlia (Current Research on Bioscences and Biotechnology, 2023)
Severe exposure to ultraviolet (UV) rays leads to skin damage, including hyperpigmentation, freckles, melanoma, age spots, and melasma, all of which are related to the skin pigment enzyme, tyrosinase. Prevention can be achieved by avoiding harsh UV rays and inhibiting tyrosinase catalytic activity. Many compounds have been developed for the treatment of such conditions; however, most come with unwanted side effects. The purpose of this study was to determine the sun protection factor (SPF) value and tyrosinase enzyme inhibitory activity of plant secondary metabolites with high antioxidant activity, namely rutin, catechin, niazirin, piperine, quercetin, and quercitrin, as potential alternatives. Both tests were carried out using UV-Vis spectrophotometry. SPF determination was performed by observing the absorbances across a wavelength range of 290 to 320 nm. The determination of anti-tyrosinase activity was conducted by measuring dopachrome at 490 nm after enzymatic reactions and calculating the IC50 value. In the SPF assay, benzophenone-3 was used as the standard, and piperine, rutin, quercetin, and quercitrin exhibited high protective abilities with SPF values above 30 at 500 µg/mL. In the tyrosinase inhibition assay, kojic acid as the standard showed a strong potential for inhibition with an IC50 of 33.65 µg/mL, while quercetin, rutin, and piperine exhibited weaker inhibitory potential with IC50 values of 178.44, 271.73, and 347.62 µg/mL, respectively. On the other hand, quercitrin and niazirin showed little to no tyrosinase inhibition activity. However, catechin demonstrated more catalytic activity towards the enzyme. In conclusion, quercetin, rutin, and piperine have the potential to be developed as active ingredients to protect the skin from UV-induced damage due to their satisfactory SPF values and tyrosinase inhibition activity.